As práticas sociopedagógicas e sua influência na formação humanística e na politização dos velhos da universidade da maturidade do câmpus de Araguaína da Universidade Federal do Tocantins - Sampaio, Miliana Augusta Pereira (2024)
Certainly, population aging deserves family, civil society and State’s attention, in order to guarantee citizenship and political and social rights in old age, aiming to dignified aging in Brazil. However, in practice, a large part of society refuses to accept that this last cycle of life is lived with integrity. In this respect, Education is a fundamental strategy to enhance the social protagonism of the elderly. As a consequence of these discussions, the guiding question of this study arises: how do socio-pedagogical practices influence the humanistic training and politicization of the elderly at the Maturity University of the Federal University of Tocantins in Araguaína? Based on this question, we sought a methodology to support this research. Thus, we opted for a case study, with a qualitative scope, consisting of bibliographical, documental, descriptive and exploratory and participatory research. This choice had the intention of knowing the socio-pedagogical practices carried out with the UMA/Araguaína academics for the humanistic formation and for the politicization of the elderly. To achieve this objective, a description of the socioeconomic and demographic profile of the UMA academics in Araguaína is presented, as well as an analysis of the political-pedagogical project of the Maturity University Campus Araguaína. In addition, an attempt was made to explain, based on the perception of professors, the influence of socio-pedagogical practices carried out with UMA/Araguaína (TO) academics in the humanistic formation and politicization of the elderly. Still, a field research in which a socioeconomic questionnaire with open and closed questions was applied, in this way, semi-structured interviews were carried out in order to give voice to the research protagonists. After the content analyses, approaching the phenomenology, it is concluded that the majority of UMA students are women, retired, from the lower middle class, who consider UMA a place that provides socialization and quality of life, as well, a space that values the life trajectories of different elderly, especially effecting citizenship and the promotion of protagonism in old age. In this context, it is observed that UMA is a space that goes beyond its educational and academic dimension. It can also be said that it is a socialized experience, which brings interpretations of aging in which knowledge is built through an integrated perception of teaching, it should be noted, not in a fragmented way. This understanding is based on popular education, which promotes a transaction of knowledge aiming to emancipation, in a positive view of aging, something vital in the face of the demographic transformations presented in the new Brazilian population pyramid. Finally, we aspire that the reflections held here make it possible to update researchers in the area and encourage the desire to deepen the potentialities and scientific gaps pointed out for an active and quality aging in the Legal Amazon.